Effect of multipurpose trees on production of large cardamom and soil fertility in agroforestry systems in Sikkim, Himalaya - Singh, Matber; Das, S.K.; Avasthe, R.K. (Indian Journal of Agroforestry, 2020)
Large cardamom cv. Sawney was planted in combination with multipurpose tree species as well as in mixed forest system, to assess growth and yield performance. The more number of spikes clump-1, capsules clump-1, fresh weight of capsule, dry weight of capsule and dry yield was significantly higher in Alnus nepalensis-based agroforestry system. The lowest growth parameters were found in open condition. Plant available macro-nutrients were significantly higher in Alnus-based agroforestry system, followed by mixed forestry system and Leucaena leucocephala. However, an accumulation of soil organic carbon content was higher in mixed forestry system, followed by Ficus-based agroforestry system. Accumulation of boron was higher in Alnus-based agroforestry. The maximum microbial biomass carbon (MBC) was recorded in mixed forest (847 mg kg-1) and lowest in control (398 mg kg-1) in the surface layer. The surface soil layer of A. nepalenesis had the maximum microbial biomass nitrogen (MBN; 416 mg kg-1) and the lowest in control (257 mg kg-1). The same trend was observed in the sub-surface layer also (309 in A. nepalenesis and 147 mg kg-1 in control). Our results will provide suitable and sustainable tree based systems for more effective large cardamom management in Sikkim mountain region and elsewhere without hampering soil fertility.